DARI DAPUR KE DASHBOARD: INTERGRASI PEWARNA ALAMI DAN SISTEM OVERHEAD DIGITAL UNTUK OPTIMALISASI UMKM KERUPUK ANTOR - Osie Listina; Wiliyanto Wiliyanto; Anisa Oktiawati; Reno Arkan Pratama (Universitas Mataram, 2026)
This program was implemented to improve the production capacity and financial management of the Kerupuk Antor MSME in Penusupan Village. The partner’s main problems include the lack of product innovation and weak recording of production costs, particularly overhead costs. The interventions carried out consist of product innovation using herbal-based ingredients and the implementation of a digitally designed system for recording production costs. The program aims to introduce innovations to Kerupuk Antor through a variety of flavors and colors derived from herbal ingredients as a form of product diversification. The intervention related to production cost calculation conducted by the team is expected to reduce losses caused by unrecorded production expenses. The activities were conducted at the Kerupuk Antor MSME in Penusupan Village over a period of four months. The methods included outreach, training, technology implementation, mentoring, and evaluation using pre-tests and post-tests with 10 assessment items consisting of 5 multiple-choice questions and 5 essay questions. Of the 29 MSME members, 26 met the criteria and agreed to participate actively in all stages of the program, with 18 respondents providing evaluable data. The scores were then analyzed descriptively using a scoring range of 0–100. The application of simple technology successfully produced Kerupuk Antor with natural coloring and distinctive flavor. The digital cost-recording training improved participants’ understanding of overhead costs, as shown by an increase in the average pre-test score from 37.10 to 97.67. This program contributes to the achievement of the SDGs, particularly in the areas of decent work, economic growth, and industrial innovation. Program implications highlight improved product competitiveness, better bookkeeping practices, and the potential for replication as a model for other local MSMEs.